Social media and libraries in scientific production in Spain - França, Maira Nani [UNESP]; Pacios, Ana R.; Grossi, Angela Maria [UNESP] (My University, 2022)
Like other cutting-edge organizations, libraries communicate with their users via social networks. The numerous experiences become known through different channels, mostly in scientific events and publications. The goal of this research is to identify the characteristics of Spanish scientific production on ‘social media and libraries’ in order to understand its evolution and trends. This is a descriptive study, based on domain analysis, as proposed by Hjørland. Fifty-four articles published in journals indexed in ÍnDICEs-CSIC and Dialnet are analyzed. This theme has been addressed by the scientific community since 2006, preferably within the scope of academic libraries. Most of the citing authors and the most cited belong to the area of Librarianship and Documentation, in collaboration with researchers, mainly from Education, Communication and Computer Engineering. The initial stage of formation of an epistemic community is identified. ‘Social networks’ is the most widely used terminology, even though ‘social media’ presents itself as a trend. It is recommended to incorporate new descriptors to update the knowledge organization schemes in the area.
Medios sociales y bibliotecas en la producción científica de España
Mídias sociais e bibliotecas na produção científica da Espanha
Keywords: Domain analysis; Social networks; Social web; Web 2.0